Analysis of the Effectiveness of the Ishlah Method and Its Influence on the Ability to Read the Al-Quran - Kristanto, Yudi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research was motivated by concerns about data in Indonesia where the majority of the population is Muslim and it turns out that 62% cannot read the Koran, then one of the clerics in Karawang, West Java Province created a method of learning to read the Koran called the Ishlah method which was implemented through the National Eradication Movement. Al-Quran illiteracy led by the general chairman KH. Mahbub Soleh Zarkasyi is also the inventor of the ishlah method. This research was carried out at the Syamira Arrasyid Islamic Foundation Karawang as a mu'allim senter or Al-Quran reading learning institution which has applied the ishlah method with a sample of 32 respondents using the Mixed Method research method through explanatory design techniques, namely a combination of quantitative and qualitative research methods. The results of quantitative research show that there is a significant influence between the application of the Ishlah Method on the ability to read the Koran. This is based on statistical calculations, a correlation coefficient of r = 0.695 and a coefficient of determination of R = r.2 = 0.483. Testing the significance of the correlation obtained tcount (5,295) > t table (1.671) at α = 0.05, indicating that the correlation coefficient is significant. Thus, the research hypothesis which states that there is a relationship between the Ishlah Method and the ability to read the Koran can be accepted. This means that the more the Ishlah Method is applied, the higher the ability to read the Koran will be. Meanwhile, the coefficient of determination of 0.483 shows that 48.3% of the variation in Al-Quran Reading Ability can be explained by variations in the Ishlah Method, the remaining 51.7% is determined by other factors outside the Ishlah Method. The results of qualitative research show that the ishlah method is very effective for teenagers, adults and the elderly because it has special characteristics which are given the acronym BISMILLAH and can stimulate the synergy of the work of the left brain and right brain so that it makes learning to read the Koran more enjoyable and not bored and unfamiliar. stratification of levels like other methods so that students who learn to read the Koran do not feel embarrassed and inferior.